Content-Aware Video Adaptation under Low-Bitrate Constraint. (2nd August 2007) - Hsiao Hsiao, Ming-Ho Ming-Ho; Chen Chen, Yi-Wen Yi-Wen; Chen Chen, Hua-Tsung Hua-Tsung; Chou Chou, Kuan-Hung Kuan-Hung; Lee Lee, Suh-Yin Suh-Yin
Abstract : With the development of wireless network and the improvement of mobile device capability, video streaming is more and more widespread in such an environment. Under the condition of limited resource and inherent constraints, appropriate video adaptations have become one of the most important and challenging issues in wireless multimedia applications. In this paper, we propose a novel content-aware video adaptation in order to effectively utilize resource and improve visual perceptual quality. First, the attention model is derived from analyzing the characteristics of brightness, location, motion vector, and energy features in compressed domain to reduce computation complexity. Then, through the integration of attention model, capability of client device and correlational statistic model, attractive regions of video scenes are derived. The information object- (IOB-) weighted rate distortion model is used for adjusting the bit allocation. Finally, the video adaptation scheme dynamically adjusts video bitstream in frame level and object level. Experimental results validate that the proposed scheme achieves better visual quality effectively and efficiently.